2016
DOI: 10.1007/s13205-016-0509-4
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of plant synergistic bacteria capable of degrading xenobiotics from oil spillage sites

Abstract: Oil spillage sites primarily contain various types of hydrocarbons, such as linear chain, polycyclic, and aromatic compounds, posing several detrimental effects on plants. Results from our previous study showed an alteration of various metabolomic parameters, indirectly resulting in an observable decline of growth in the mung seedlings upon incubation with phenol, toluene, xylene, and hexane. This study evaluates the role of these compounds upon plant growth and focusses to mitigate the effect of the same, usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Whereas various factors must be taken into considered before in situ bioremediation, it includes nature as well as concentration of contaminated oil in the prevalent climate condition such as sources of environment contamination and the nutrient content of soil-water along with pH of the contaminated-site (13,56). Furthermore, research can be directed for exploring the participation of individual microbe in impacting the effectiveness of a microorganism association along with optimal degradation conditions under in situ conditions respectively (57).…”
Section: Bacterial Growth Kinetic Studymentioning
confidence: 99%
“…Whereas various factors must be taken into considered before in situ bioremediation, it includes nature as well as concentration of contaminated oil in the prevalent climate condition such as sources of environment contamination and the nutrient content of soil-water along with pH of the contaminated-site (13,56). Furthermore, research can be directed for exploring the participation of individual microbe in impacting the effectiveness of a microorganism association along with optimal degradation conditions under in situ conditions respectively (57).…”
Section: Bacterial Growth Kinetic Studymentioning
confidence: 99%
“…having high growth as compared than other test organisms and reported Bacillus cereusas most tolerant to withstand high levels of hydrocarbon in the soil due to the presence of endospore Annweiller et al (2000). A study demonstrated that the bacterial consortium (BC) of Acinetobacter, Flavobacterium, Pseudomonas and Serratiaas hydrocarbon-utilizers De and Gupta (2016); Atlas (1981). Samples were incubated in orbital shaking incubator at 37 o C at 125rpm up to 15days and theamount of petroleum-hydrocarbon degradation was estimated by gravimetric analysis at each 5 days interval.…”
Section: Bacterial Growth Kinetic Studymentioning
confidence: 99%
“…Some studies reported, that the inoculation had positive/marginal/no effects on rate of oil biodegradation.Whereas,various factors must be taken into considered before in situ bio-remediation, it includesnatureas well as concentration of contaminated oil in the prevalent climate condition such as sources of environment contamination and the nutrient content of soil-water along with pH of the contaminated-site Dixit et al (2015); Rosenberg (1992). Furthermore research can be directed forexploring the participation of individual microbe in impacting the effectiveness of a microorganismassociationalong with optimal degradation conditions under in situ conditions respectively De and Gupta (2016).…”
Section: Bacterial Growth Kinetic Studymentioning
confidence: 99%
“…These families are: Enterobacteriaceae, Enterococcaceae, and Pseudomonadaceae ( Figure 1 ). We can hypothesize that these families were present in all of the insects investigated mainly because of their metabolic versatility and ability to help the insect overcome and degrade different complex compounds produced by plants [ 53 , 67 ].…”
Section: Microbiota Of Moth Pestsmentioning
confidence: 99%